Task-Based Language Teaching in Hospitality Training - Purwanto, M Bambang; Despita, Despita; Auliana, Nyayu Ully (Asian Journal of Applied Education (AJAE), 2024)
This study aims to measure the effectiveness of implementing Task-Based Language Teaching (TBLT) in improving the English language skills of Palembang Hospitality Job Training Institute (LPK) students who will intern at hotels. This research mainly focuses on the speaking and listening skills needed in direct interaction with foreign guests in the hotel environment. This study uses a descriptive qualitative method, with data collected through pre-tests and post-tests on 10 students. The results showed that the average pre-test score of students was 62.8, while the average post-test score increased to 86.1, with an average increase of 23.3 points. This increase shows that implementing TBLT effectively improves students' English proficiency, especially in the context of practical communication relevant to the hospitality industry. Students also reported increased confidence in using English after training due to a task-based learning approach that allowed them to practice in real-life situations. Although the results were positive, the study had some limitations, such as a limited sample size and a short duration of training. This study has implications that TBLT can be implemented more widely in other LPKs that focus on the hospitality sector, and it is recommended that follow-up research with a larger sample and longer training time be conducted to obtain more comprehensive results.